(untitled) (Universal International Scientific Journal, 2026)
In the pedagogy of music education, the aspects of the connection between the science of music and music pedagogy in the early stages of musical development are highlighted by the research and results of scientists. During the period of pedagogical activity, the issues of educating students and instilling in them the foundations of the science are well-founded.